Experimental characterisation of active and non‐active harmonic power flow of AC rolling stock and interaction with the supply network - Andrea Mariscotti (IET Electrical Systems in Transportation)
Abstract In AC electrified railways, there is a significant exchange of power at fundamental and harmonics in quite dynamic conditions. Harmonic patterns of AC rolling stock and railway networks are analysed in terms of active and non‐active power flow, relating it to the characteristic of the network and to operating conditions, synthesised in the fundamental current intensity and speed. Herein, it is shown that correlation and clustering can separate distortion terms of internal and external origin also without a priori information. The use of harmonic power terms (product of voltage and current components) shows improved robustness with respect to the analysis of the voltage and current components alone.